First asymmetric total synthesis of aspinolide A - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
The first total synthesis of aspinolide A has been achieved using ring-closing metathesis as a key step. The stereogenic centers were generated by means of hydrolytic kinetic resolution (HKR) of racemic epoxides. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis